Role of p63 and the Notch pathway in cochlea development and sensorineural deafness. - Terrinoni, A; Serra, V; Bruno, E; Strasser, A; Valente, E; Flores, E; van Bokhoven, H; Lu, X; Knight, R; Melino, G (2013)
The ectodermal dysplasias are a group of inherited autosomal dominant syndromes associated with heterozygous mutations in the Tumor Protein p63 (TRP63) gene. Here we show that, in addition to their epidermal pathology, a proportion of these patients have distinct levels of deafness. Accordingly, p63 null mouse embryos show marked cochlea abnormalities, and the transactivating isoform of p63 (TAp63) protein is normally found in the organ of Corti. TAp63 transactivates hairy and enhancer of split 5 (Hes5) and atonal homolog 1 (Atoh1), components of the Notch pathway, known to be involved in cochlear neuroepithelial development. Strikingly, p63 null mice show morphological defects of the organ of Corti, with supernumerary hair cells, as also reported for Hes5 null mice. This phenotype is related to loss of a differentiation property of TAp63 and not to loss of its proapoptotic function, because cochleas in mice lacking the critical Bcl-2 homology domain (BH-3) inducers of p53- and p63-mediated apoptosis--Puma, Noxa, or both--are normal. Collectively, these data demonstrate that TAp63, acting via the Notch pathway, is crucial for the development of the organ of Corti, providing a molecular explanation for the sensorineural deafness in ectodermal dysplasia patients with TRP63 mutations.